Classification of Acceleration Waveforms during Walking by Wavelet Transform - Tamura, T.; Sekine, M.; Ogawa, M.; Togawa, T.; Fukui, Y. (Methods of Information in Medicine, 1997)
In this study we have attempted to classify the acceleration signal, while walking both at horizontal level, and upstairs and downstairs, using wavelet analysis. The acceleration signal close to the body’s center of gravity was measured while the subjects walked in a corridor and up and down a stairway. The data for four steps were analyzed and the Daubecies 3 wavelet transform was applied to the sequential data. The variables to be discriminated were the waveforms related to levels -4 and -5. The sum of the square values at each step was compared at levels -4 and -5. Downstairs walking could be discriminated from other types of walking, showing the largest value for level -5. Walking at horizontal level was compared with upstairs walking for level -4. It was possible to discriminate the continuous dynamic responses to walking by the wavelet transform.
Keywords: Gait; Acceleration; Classification; Wavelet Transform